Epidemiology and classification of lumbosacral spondylolisthesis – part II - Wójcik, Gustaw (Journal of Education, Health and Sport, 2017)
Spondylolisthesis is a complex and variable disease pathophysiological entity that has long been the subject of numerous investigations. The complexity of the disorder and the variety of treatment methods require an effective classification system that is easy to remember and use in practice. Classification systems have undergone many modifications ranging from Meyerding’s system by Taylard, Newman, Wiltse, Meschan to the Spine Deformity Study Group (SDSG), whose formulation seems to be complex, but is simple to use. Many classification systems are still widely used so different treatment strategies can be defined. Hence the knowledge of individual systems is required for effective recognition and treatment of this defect of the spine. This article discusses several successive classification systems for vertebral grading, which are in addition to the previously presented classification.